2016
DOI: 10.3390/ijms17111780
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Promotes Tendon-Bone Healing during Repair of Rotator Cuff Tears: A Biomechanical and Histological Study

Abstract: To investigate whether the systematic administration of icariin (ICA) promotes tendon-bone healing after rotator cuff reconstruction in vivo, a total of 64 male Sprague Dawley rats were used in a rotator cuff injury model and underwent rotator cuff reconstruction (bone tunnel suture fixation). Rats from the ICA group (n = 32) were gavage-fed daily with ICA at 0.125 mg/g, while rats in the control group (n = 32) received saline only. Micro-computed tomography, biomechanical tests, serum ELISA (calcium; Ca, alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…In the present study, delayed healing and decreased VEGF were found after injection of ZA and DX, while improved healing and promoted VEGF were noted after the intervention of a high dose of ICA. Previous studies have shown that ICA promoted VEGF and ZA inhibited wound healing and the expression of VEGF, which were in accordance with our study. VEGF is one of the growth factors that are of great importance in soft tissue repair and angiogenesis .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, delayed healing and decreased VEGF were found after injection of ZA and DX, while improved healing and promoted VEGF were noted after the intervention of a high dose of ICA. Previous studies have shown that ICA promoted VEGF and ZA inhibited wound healing and the expression of VEGF, which were in accordance with our study. VEGF is one of the growth factors that are of great importance in soft tissue repair and angiogenesis .…”
Section: Discussionsupporting
confidence: 93%
“…The stimulative effect of icarrin on wound healing have been confirmed by other studies 13,20,21 and this may correlate to upregulated expression of VEGF which correlates to angiogenesis, 22 activated the MEK/ERK and PI3K/Akt/eNOS‐dependent signal pathways and promoted differention of keratinocyte involved in wound healing 13,20,23 . Angiogenesis is also an important factor in bone healing 12 and studies have shown the promising effect of icarrin on bone healing via promoting angiogenesis 11,24 . Besides, inflamation could delay soft tissue healing and the anti‐inflammatory effect of icarrin was also proved 25,26 .…”
Section: Discussionmentioning
confidence: 77%
“…One longitudinal half of the tendon was used to evaluate angiogenesis indirectly by measuring the tissue's hemoglobin content as a percentage of wet tissue weight on the day of euthanasia. 39 The tissue's DNA content and proteoglycan (PG) content, both as a percentage of wet tissue weight, were also evaluated as measures of tissue repair on the homogenized tissue after freezing samples at -80 C. Samples were frozen with liquid nitrogen, and a tissue pulverizer (Cellcrusher) was used to homogenize the tissue. Homogenate from each sample was then centrifuged for 5 minutes at 13,000 rpm with 1 mL of 0.2% Triton X-100 cell lysis buffer (Sigma-Aldrich).…”
Section: Assaysmentioning
confidence: 99%